Accipitrinae Vieillot 1816 - James, Helen F. (Zenodo, 2020)
Accipitrinae Aquila chrysaetos (Linnaeus) / A. bivia Emslie & Czaplewski 1999 Material. CM 34018, r ungual phalanx with tip and base missing. Description. Corresponds in size and shape with the terminal phalanx of digits one (the hind toe) and two of an eagle. Brodkorb & Mourer-Chauviré (1984) referred it to A. chrysaetos rather than H. leucocephalus based on large overall size and more gentle distal tapering of the claw core (plantar view), implying a longer claw. Based on these criteria, I found it to be larger than all comparative specimens of H. leucocephalus and most comparative skeletons of A. chrysaetos. It agrees well in size and shape with one comparative skeleton of A. chrysaetos (USNM BIRDS 19724). However, the possibility that it belongs to the larger early Irvingtonian species Aquila bivia cannot be excluded. Remarks. This large ungual phalanx appears to be attributable either to the Golden Eagle ( A. chrysaetos ) or to a larger, early Irvingtonian species of Aquila described from Florida and Arizona (Emslie & Czaplewski 1999). The modern distribution of the Golden Eagle in North America is primarily in the west, but the species does have a rarely observed wintering population in the region of Cumberland Bone Cave (Brodeur et al. 1996). : Published as part of James, Helen F., 2020, The Irvingtonian Avifauna of Cumberland Bone Cave, Maryland, pp. 111-131 in Zootaxa 4772 (1) on pages 119-120, DOI: 10.11646/zootaxa.4772.1.4, http://zenodo.org/record/3814013 : {"references": ["Emslie, S. D. & Czaplewski, N. J. (1999) Two new fossil eagles from the late Pliocene (late Blancan) of Florida and Arizona and their biogeographic implications. Smithsonian Contributions to Paleobiology, 89, 185 - 198.", "Brodkorb, P. & Mourer-Chauvire, C. (1984) Pleistocene Birds from Cumberland Cave, Maryland. In: Genoways, H. H. & Dawson, M. R. (Eds.), Contributions in Quaternary Vertebrate Paleontology: A Volume in Memorial to John E. Guilday. Carnegie Museum of Natural History, Special Publication No. 8, pp. 39 - 43.", "Brodeur, S., Decarie, R., Bird, D. M. & Fuller, M. (1996) Complete migration cycle of Golden Eagles breeding in northern Quebec. The Condor, 98, 293 - 299. https: // doi. org / 10.2307 / 1369147"]}